”Kyrkan förvaltar, äger 460 tusen hektar av skapelsen” : En kvalitativ innehållsanalys av samiska perspektiv på försoningsprocessen mellan Svenska kyrkan och det samiska folket. - Björnström, Laila (Karlstads universitet, Institutionen för samhälls- och kulturvetenskap (from 2013), 2023)
This essay examines Sami perspectives on the reconciliation process between the Sami people and the church of Sweden. This is based on a qualitative content analysis of the recitals during the Ságastallamat conference in October 2022 that brought together Sami and church representatives. Theoretically, the essay is based on a model for reconciliation in post-colonial societies developed by Verdeja (2017). Reconciliation is understood according to this model as divided into four concepts, critical reflection, symbolic recognition, material recognition, and political participation. The result shows that the concepts applied to the Sami perspectives that emerged during Ságastallamat 2. The Sami representatives expressed that all four concepts were needed for reconciliation to be reached. A point at issue that emerged as particularly important in all parts of the reconciliation model was the land issue and self-determination. This was connected to critical reflection since it was considered that the self-determination of Sami´s land had been lost through colonization. It was also connected to symbolic recognition as the church was prompted to take a stand for the Sami to regain lost land. The fact that the church of Sweden owns land was connected to material recognition as the church was urged to return the land to the Sami. Finally, the issue of land was connected to political participation since it was considered that the Sami should be given self-determination over land and that within the church one should use Sami knowledge to manage the creation.